Perancangan Sistem Informasi Kerjasama Pada Fakultas Teknik Universitas Sebelas Maret Surakarta. - Muryono, Langgeng; Hastomo, Mursid Dwi; Wibowo, Kresno Ario Tri (Indonesian Journal of Information Technology and Computing (IMAGING), 2023)
The Faculty of Engineering, Universitas Sebelas Maret Surakarta (UNS) cooperates with various external parties. The recording and archiving of collaboration data is already using a computer by utilizing the Microsoft Excel application. This collaboration data recording system needs to be improved by switching to a website-based information system. It aims to facilitate the search for cooperation data, recording cooperation data and making cooperation reports. By utilizing the website, collaboration data can be accessed at any time without having to search for the physical files. Based on the problems above, the authors formulate the problem to be solved in this study is "How to design a collaborative information system at the Faculty of Engineering UNS". So that this research does not widen, the authors provide limitations on problems related to the design of a collaborative information system made specifically for the Faculty of Engineering, UNS. The collaborative information system design method is the Development Life Cycle System (SDLC) with the Waterfall model. The programming language used is PHP Native and MySQL database for data storage. The purpose of this research is to facilitate cooperation units of the Faculty of Engineering UNS in terms of managing collaboration data including recording, archiving and recapitulating cooperation reports. With the design of this cooperation information system, it is hoped that it will make it easier for the cooperative unit to manage collaboration data at the Faculty of Engineering, UNS